إطلاق مصطلح أقسام الكلام للاسم والفعل والحرف عند النحويين بين القبول والاعتراض - jamal, danial; Jailani ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2022)
Everyscientific disciplinehas special terms that characterize it. Sometimes it is found in a scientific discipline where the terms used sometimes have different meanings between one expert and another due to differences in their point of view and level of expertise. Likewise, in Nahwu science, there are several terms that differ in understanding among Nahwu scholars, either personally, in groups, or in schools of thought. Among these terms is the term "Aqsam al-Kalam" which is used to indicate the scope of Isim, Fi'il and Letters in Arabic sentences (al-Kalam). This paper aims to explain the differences in meaning that developed among Nahwu Ulama of the term "Aqsam al-Kalam".